Magnesium recurarisation differences between no reversal, neostigmine/glycopyrrolate reversal and sugammadex reversal of neuromuscular block in an in vivo rat model - Van den Berg, Maurits Matthew (Department of Human Biology, 2016)
The neuromuscular junction (NMJ) is a synapse with one of the highest safety margins in the human body. The use of neuromuscular blocking agents to inhibit neuromuscular transmission is sufficient to produce skeletal muscle paralysis, a mechanism used to facilitate muscle relaxation during surgery. Residual neuromuscular block postoperatively has been found to be a major risk factor for postoperative complications. Sudden reinstatement of neuromuscular block (recurarisation), through use of magnesium, has also been observed clinically. This has led to a reluctance to use magnesium postoperatively for fear of recurarisation. Recurarisation following reversal of neuromuscular blockade with neostigmine or sugammadex has not been evaluated in a formal study, and for this reason, this study investigated recurarisation after 30 mg/kg magnesium sulphate (MgSO4) following reversal of neuromuscular blockade with neostigmine, two dosages of sugammadex or when reversal was omitted. Prior to investigating recurarisation, the effects of magnesium on neuromuscular transmission in the absence of neuromuscular blocking agents was investigated, in order to determine a standard clinical dose that did not produce detectable, by Train-of-Four Ratio (TOF-R) or Twitch 1 height (%T1), neuromuscular impairment.